Postoperative Pain and Urinary Retention After Vaginal Reconstructive Surgery. Issue 3 (March 2021) - Yadav, Menaka; Patel, Kunal; Turrentine, Mark A.; Orejuela, Francisco; Jackson, Elisha; Kilpatrick, Charles
Abstract : Objective: The objective of this study was to evaluate the effect of patients' immediate prevoiding pain level after vaginal pelvic reconstructive surgery on their ability to void. Methods: We conducted a retrospective cohort study of women with and without urinary retention after urogynecologic procedures. Postoperative pain, measured by a visual analog scale, was recorded for each patient before a voiding trial. Demographic, surgical characteristics, prevoiding trial pain, and rate of postoperative urinary retention were compared. Multiple-logistic regression analysis was used with all analyses controlled for univariate variables with a P value of ≤0.1 to estimate adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Two-tailed tests were used, with P < 0.05. Results: A total of 458 patients were identified, of which 21% (97/458) failed their voiding trial. In our study, 62% (284/458) of women had a voiding trial on postoperative day 1, and 38% (174/458) underwent a same-day voiding trial. No differences were noted between groups comparing race, ethnicity, hysterectomy, urinary sling, estimated surgical blood loss, utilization of intraoperative or postoperative narcotics, or the proportion of same-day voiding trials. Women with postoperative urinary retention had higher mean prevoiding pain when compared with women without urinary retention (pain visual analog scale, 25 mm vs 12 mm [ P < 0.001], respectively). After multiple-logistic regression analysis, a significant association between postoperative urinary retention persisted for prevoiding trial pain score (aOR, 1.02; 95% CI, 1.01–1.03), age (aOR, 1.05; 95% CI, 1.02–1.02), and anterior colporrhaphy (aOR, 2.13; 95% CI, 1.18–3.8). Conclusions: Prevoiding pain after pelvic surgery is significantly associated with increased rates of postoperative urinary retention.